Moral Conflicts in Squid Game Movie - Musdalifah Alpita; Bima Prana Chitra; Hidayati Hidayati (REGISTER: Journal of English Language Teaching of FBS-Unimed, 2022)
This study aims to analyze the moral values in the conflict squid game movie, namely the values of survival strategies, self-sacrifice, cooperation, egoism, and values contained in conflict. In conflict, there are morals that we can reflect on ourselves in everyday life, and these moral values are often found in experiences, events and even stories. The research method used is a qualitative method by selecting dialogues that contain moral elements in the conflict. And the descriptions are written using dynamic structuralism by Levi Strauss, Wallek and Warren to express the idea of moral values in conflict in the selected dialogues. The results of this study show that the moral characters that can be described in the Squid game movie by Hwang Dong Hyuk consistently show how to survive, be willing to sacrifice and make conflict a good moral value in everyday life.Keywords : Moral, Survival,Self-sacrifice